2018
DOI: 10.5664/jcsm.7046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bedroom Environmental Conditions on the Severity of Obstructive Sleep Apnea

Abstract: Elevation of PM concentration is significantly associated with increased OSA severity. Our findings suggest that reduction in exposure to particulate matter and suitable bedroom environments may lessen the severity of OSA and promote good sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 41 publications
(63 reference statements)
0
14
1
Order By: Relevance
“…A recent study showed that household air pollution due to solid fuel combustion was associated with poor sleep among the elderly [22]. Furthermore, although we did not observe any association between indoor conditions and chronotype in our study, indoor air quality (such as odour, airflow, and improper ventilation) was also found to be associated with poor sleep quality and increased risk of sleep apnoea [14][15][16][17]. Reducing the use of solid fuel was observed to improve respiratory and sleep symptoms in children [23].…”
Section: Summary Of the Findings And Its Contextual Relevancecontrasting
confidence: 82%
See 1 more Smart Citation
“…A recent study showed that household air pollution due to solid fuel combustion was associated with poor sleep among the elderly [22]. Furthermore, although we did not observe any association between indoor conditions and chronotype in our study, indoor air quality (such as odour, airflow, and improper ventilation) was also found to be associated with poor sleep quality and increased risk of sleep apnoea [14][15][16][17]. Reducing the use of solid fuel was observed to improve respiratory and sleep symptoms in children [23].…”
Section: Summary Of the Findings And Its Contextual Relevancecontrasting
confidence: 82%
“…Living in rural areas compared to urban areas is associated with higher morningness [13]. Recent evidence suggests that residential proximity to industry, exposure to second-hand smoke (SHS), inappropriate indoor environment, and use of biomass cooking fuel were associated with sleep disturbance [14][15][16][17][18][19][20][21][22][23]. Biomass cooking fuel is a well-known risk factor for several chronic respiratory and cardiac diseases [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…However, adherence was worst in summer in this study. Researchers have suggested that a summertime increase in the residual respiratory disturbance index due to air pollution (i.e., elevated particle pollution) directly influences upper-airway inflammatory responses, with increases in upper-airway resistance and collapsibility [25,26]. However, this factor is not applicable to the present study, which was conducted in a region with no air pollution problem.…”
Section: Discussionmentioning
confidence: 78%
“… 21 Sleep deprivation, in turn can increased central sympathetic outflow, 39 which over time can increase blood pressure and induce insulin resistance. 40 Dry air can exacerbate snoring 41 ; in middle-aged men snoring is common, as is obstructive sleep apnea, which can trigger nocturnal CVD events. 42…”
Section: Discussionmentioning
confidence: 99%